English Textbook Analysis for Governmental Studies From Students’ Responses - Kurniawati, Layla; Kulachai, Waiphot (Universitas Islam Negeri Raden Intan Lampung, 2024)
The different English materials among the IPDN lecturers made English materials do not have standards. Therefore, it initiates the English lecturers to create English textbooks. This research aims to know the use of the English textbook from the student's perspective. This study used a descriptive qualitative method with a technique for collecting data via questionnaires which are distributed to 202 students via Google Forms. The interviews are also used to know the students’ responses using the textbook. There are some findings: 1). Most of the respondents agree the materials in the form of reading text and focus on Government science; 2). 83,4% (168) agree with governmental topics, 16,6% (34) students disagree; 3) Tasks and activities provide opportunities to improve reading comprehension in English as well as other English language proficiency and government science; 4). Tasks and activities are coherent; 5). There are some strategies for learning English reading, such as Guessing in the form of schematic Theory and Collaboration for learning English together among the students in their dormitory